Avaliação do sistema auditivo e da cognição de pacientes idosos usuários de aparelhos de amplificação sonora individual - AZEREDO, Dulcineia Sampaio (2019)
Introduction: Hearing is a communication tool, and one of extreme importance to all human beings. As one gets old, a natural hearing deficit comes up, the presbycusis. Considering the elderly population growth in all over the world, hearing aids have become more and more popular in order to diminish the negative impact of hearing losses on this population. Objectives: To evaluate the benefits obtained by elderly patients from the use of hearing aids and to assess their cognitive function through the Mini Mental State Examination (MMSE). Methods: A prospective study was performed with 26 elderly people, who started to use hearing aids, and then answered the MMSE test. After three to six months, the MMSE was reapplied. Results: The analysis of scores before and after the hearing aid fitting demonstrated improvement of cognitive function after the use of the devices. By sorting the groups according to educational level, illiterate patients were not benefited (p>0,05); and as to the type of service used, more benefits were obtained by private clinics users. Conclusion: This study results present the cognitive benefit obtained through the use of hearing aids.